The Investment Climate in 16 Indian States - Iarossi, Giuseppe (2012)
In this paper, the author attempts to identify the characteristics of the business climate in India that can help explain the different performance of individual states in terms of investment and growth. The paper develops a new Investment Climate Index aimed at summarizing the aspects of the business environment that entrepreneurs consider when deciding whether to invest. Using this index, the author explores the investment climate in several typologies of Indian states and identify the key features of a poor business environment in India. The analysis shows that infrastructure and institutions remain the main bottlenecks in the country's private sector development. More specifically, power, transportation, corruption, tax regulations, and theft are major factors explaining the poor business environment in some Indian states. Infrastructure appears to be the single most important constraint, as it is particularly binding in states that show low levels of domestic investment and GDP growth.